Analysis of Public Service Standards Implementation at Tegal Kunir Kidul Village Office, Mauk District, Tangerang Regency - Muhammad Rosul Asmawi; Seno Santoso (UNIVERSITAS ISLAM SYEKH YUSUF, 2026)
Public service is one of the main functions of government in meeting the needs of the community. The Tegal Kunir Kidul Village Office, as a governmental unit at the village level, plays an important role in providing administrative services to the community. This study aims to determine how the implementation of public service standards is carried out at the Tegal Kunir Kidul Village Office, Mauk District, Tangerang Regency. The method used in this research is a descriptive approach through observation of the service processes taking place at the village office. The results of the study show that although the office facilities and infrastructure are still relatively simple, services to the community continue to function with the presence of officers handling various administrative needs such as issuing certificates, providing administrative introduction letters related to population administration, and delivering information services. The implementation of public service standards has been carried out at a basic level; however, several aspects still need improvement, particularly supporting service facilities. Keywords: public service, service standards, village office.